2013
DOI: 10.1371/journal.pcbi.1002848
|View full text |Cite
|
Sign up to set email alerts
|

Network Self-Organization Explains the Statistics and Dynamics of Synaptic Connection Strengths in Cortex

Abstract: The information processing abilities of neural circuits arise from their synaptic connection patterns. Understanding the laws governing these connectivity patterns is essential for understanding brain function. The overall distribution of synaptic strengths of local excitatory connections in cortex and hippocampus is long-tailed, exhibiting a small number of synaptic connections of very large efficacy. At the same time, new synaptic connections are constantly being created and individual synaptic connection st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

21
133
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 96 publications
(155 citation statements)
references
References 34 publications
21
133
0
1
Order By: Relevance
“…5A-B), as was shown before in [20] and [18] , in which eSTDP and SN were 316 complemented with structural plasticity. We here use a different approach, leaving out 317 structural plasticity, but applying a small bias in the eSTDP rule, in favour of 318 potentiation.…”
supporting
confidence: 64%
See 2 more Smart Citations
“…5A-B), as was shown before in [20] and [18] , in which eSTDP and SN were 316 complemented with structural plasticity. We here use a different approach, leaving out 317 structural plasticity, but applying a small bias in the eSTDP rule, in favour of 318 potentiation.…”
supporting
confidence: 64%
“…Lognormal-like distributions have been observed in the weights of cortical [5,8] [18,23,56]). We conclude that I-E and E-E 344 weights in our network may form through the combination of potentiating STDP and 345 SN a right-skewed long-tailed distribution that resembles a lognormal distribution, but 346 as in the experimental observations, is not in fact precisely and entirely lognormal.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…For example, it has been shown that the age (Grutzendler et al, 2002;Trachtenberg et al, 2002;Holtmaat et al, 2005;Zuo et al, 2005;Keck et al, 2008) and size (Grutzendler et al, 2002;Holtmaat et al, 2005;Zuo et al, 2005;Majewska et al, 2006) of the spine are negatively correlated with its turnover rate. This suggests that distinct morphological features of a spine could be used as predictors of their stability.…”
Section: Introductionmentioning
confidence: 99%
“…Various regulatory mechanisms preventing this instability have been proposed theoretically [14,31,[33][34][35][36] and found experimentally [37][38][39]. Synaptic scaling [37,40] operates on a timescale of hours to days [38] by reducing all the afferent synapses to a given neuron by the same amount so that relative differences in synaptic strengths are preserved.…”
Section: Discussionmentioning
confidence: 99%